Saliva as a source of antibodies for MMR vaccine screening in teenagers - Barbara Fialho Carvalho Sampaio; Luciana Regina Meireles; Heitor Franco de Andrade (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
The use of safe and effective vaccines is a well-established public health intervention, with a major impact on the fall in the prevalence of infectious diseases. In the absence of environmental transmission, vaccines do not work for life, as originally detected. This has now generated the occurrence of vaccinated susceptible people, which allows the importation of diseases, since vaccination coverage does not equate to population immunity. The serological control of the vaccination status and the protection of a population is essential, and its execution is not friendly due to the blood collection necessary for the tests. In these assays, the specific IgG for the vaccine agent is quantified, it would be important to detect IgA as well. This is an immunoglobulin secreted for mucous membranes that neutralizes or directs the agent to non-permissive neutrophils, it is very important in vaccine protection, but difficult to detect and quantify. Saliva can be a friendly alternative material as a source of IgA and IgG for use in conventional tests and its obtainment is not invasive, facilitating the acceptance of these studies in protected groups. We standardized assays with detection of antibodies in solid phase, to prospect for effective vaccine coverage in adolescents using saliva as a biological fluid. Once established and standardized, these techniques will allow for eventual vaccine control without the need for aversive blood collection, adequate public health measures, such as revaccination, can be adequately planned.